An accidental death caused by an unexploded 40-mm grenade - Dulger, HE; Tokdemir, M (Assn Military Surg Us, 2001)
Unexploded grenades are potentially dangerous materials. Numerous grenades have been found to be unexploded after wars have ended. We present an interesting case of an unexploded grenade that was found accidentally in a soldier's skull. On physical examination, the entrance wound of an unusual penetrating object was noted. This unusual physical finding led us to undertake radiographic examination. A 40-mm unexploded grenade was noticed on the radiograph of the soldier's skull.
Keywords: Firearm Fatalities; Injuries; Suicide; Fractures; Direction; Gunshots; Homicide; Bullets; Rates; Head